2007
DOI: 10.1111/j.1365-3083.2006.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood CD161+ T Cells from Asthmatic Patients are Activated During Asthma Attack and Predominantly Produce IFN‐γ

Abstract: In humans, T cells expressing the CD161 molecule NKR‐P1A constitute around 20% of the circulating CD3+ cells and are potentially immunoregulatory in several diseases. Their role in asthma is not well known, but they could participate in asthma attacks. To determinate whether activation of CD161+ T cells and their cytokine production correlate with clinical status of asthma, we analysed blood samples from asthma attack patients (AAP) and stable asthma patients (SAP) in comparison with healthy non‐atopic control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…No previous study has reported the frequency of the resident CD3 + CD161 + T cell subset under non-inflamed conditions in bronchoalveolar space. The frequency of CD161 + cells that we observed in the blood was consistent with previous reports [ 8 , 21 23 ]. The frequency of CD3 + CD161 + T cells has been assessed and was found at increased proportions in the liver, colon, epithelium, and duodenum [ 8 10 ]; however, these studies were performed on patients with cancer, and those who had undergone liver transplantation or had gastrointestinal symptoms [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…No previous study has reported the frequency of the resident CD3 + CD161 + T cell subset under non-inflamed conditions in bronchoalveolar space. The frequency of CD161 + cells that we observed in the blood was consistent with previous reports [ 8 , 21 23 ]. The frequency of CD3 + CD161 + T cells has been assessed and was found at increased proportions in the liver, colon, epithelium, and duodenum [ 8 10 ]; however, these studies were performed on patients with cancer, and those who had undergone liver transplantation or had gastrointestinal symptoms [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, CD161 + T-cells and CD94 + T-cells accounted for approximately 12% of the total CD3 + T-cell population in healthy subjects, consistent with previous reports [4143]. There were fewer CD56 + T-cells than either CD161 + T-cells or CD94 + T-cells; again consistent with previous findings [44].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the systemic involvement, asthma exacerbation can also be monitored or even predicted by urinary metabolites including arachidonic derivatives such as leukotrienes (184,185) and urinary trypsin inhibitor (186). Exacerbated allergic asthma is accompanied with increased BAL levels of quinolinic acid, tryptophan, ECP, eosinophils (187), decreased CD29 (32) and CD44 (188) on eosinophils and elevated CD203c expression on basophils, which decreases significantly during remission (101 (189). While early or mild conditions are well-reflected local biomarkers, it appears that moderate to severe disease conditions are even visible in the peripheral blood.…”
Section: Biomarkers For Disease Severity and Exacerbationmentioning
confidence: 99%